Penerapan model inkuiri terbimbing berbantuan aplikasi powtoon terhadap hasil belajar siswa pada materi usaha dan energi di kelas X SMA Negeri 2 Percut Sei Tuan - Dea Estefania; Sabani Sabani (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2026)
Abstract The low physics learning outcomes of students are triggered by the use of conventional learning models and the minimal use of innovative learning media. This study aims to review whether the learning outcomes of students taught using the guided inquiry model with Powtoon media are higher than the learning outcomes of students taught using conventional learning models on the material of work and energy at SMA Negeri 2 Percut Sei Tuan. The research method applies a quasi-experimental two-group pretest-posttest design. The research sample with simple random sampling includes two classes, namely class X-G as an experimental class taught using the guided inquiry model assisted by Powtoon and class X-H as a control class using conventional learning. The research instrument in the form of a multiple-choice test of 15 questions was given through a pretest and posttest to review student learning outcomes. Data collection techniques were carried out through tests. Data analysis techniques applied normality tests, homogeneity tests and hypothesis tests. The results showed that the average post-test score for the experimental class was 81.437, while the control class was 71.875. A one-tailed hypothesis test then conducted, showing a significant difference in the learning outcomes of students in the experimental and control classes, where the average post-test score for the experimental class was higher than that of the control class. This shows that the implementation of the guided inquiry model assisted by Powtoon is effective in improving student learning outcomes. Therefore, the use of innovative learning models supported by interactive media can be an appropriate alternative to improve the quality of physics learning in schools.Keywords: guided inquiry; powtoon; learning outcomes; physics education; work and energy. AbstrakRendahnya hasil belajar fisika siswa yang dipicu pemanfaatan model belajar konvensional dan minimnya pemanfaatan media belajar inovatif. Penelitian ini bertujuan untuk meninjau apakah hasil belajar peserta didik yang diajar menggunakan model inkuiri terbimbing dengan media Powtoon lebih tinggi dibandingkan dengan hasil belajar siswa yang diajar menggunakan model pembelajaran konvensional pada materi usaha dan energi di SMA Negeri 2 Percut Sei Tuan. Metode penelitian menerapkan quasi eksperimen berdesain two group pretest-posttest. Populasi dalam penelitian ini seluruh siswa kelas X SMA Negeri 2 Percut Sei Tuan sebanyak 8 kelas, dimana setiap kelas berjumlah 32 orang siswa. Sampel penelitian dengan teknik cluster random sampling mencakup dua kelas, yaitu kelas X IPA G sebagai kelas eksperimen yang diajarkan memakai model inkuiri terbimbing dibantu Powtoon serta kelas X IPA H sebagai kelas kontrol memakai pembelajaran konvensional. Instrumen penelitian berupa tes pilihan ganda sebanyak 15 soal. Teknik pengumpulan data dilakukan dengan memberikan soal tes berupa pretest dan posttest. Teknik analisis data menerapkan uji normalitas, Uji homogenitas serta uji hipotesis. Hasil penelitian memperlihatkan nilai rerata postest kelas eksperimen 81.437 sementara kelas kontrol 71.875 lalu dilaksanakan uji hipotesis satu pihak ada beda signifikan pada hasil belajar siswa kelas eksperimen serta kelas kontrol, di mana nilai rerata posttest kelas eksperimen lebih tinggi dibanding kelas kontrol. Hal ini memperlihatkan implementasi model inkuiri terbimbing dibantu Powtoon efektif menaikkan hasil belajar siswa. Dengan begitu, pemanfaatan model belajar inovatif yang didukung media interaktif bisa dijadikan alternatif yang tepat guna membangkitkan mutu belajar fisika di sekolah.Kata kunci: inkuiri terbimbing; media Powtoon; hasil belajar; pembelajaran fisika; quasi eksperimen.